Seismic design for reinforced concrete hospital building influenced by level of peak ground acceleration and class of ductility - Farashaheeda, Ahmad Jani (2018)
A series of earthquakes such as Sumatra-Andaman earthquake on 26 December 2004, Nias earthquake on 28 March 2005, and Bengkulu earthquake on 12 December 2007 had influences to a series of subsequence local earthquake in Peninsular Malaysia. Some of the local earthquake that had been affected are at Bukit Tinggi on 30 November 2007 to 25 May 2008, Jerantut on 17 March 2009, Manjong on 29 April 2009, and Kuala Pilah on 29 and 30 November 2009. While in East of Malaysia especially Sabah, it is locally known as earthquake prone region. Hence it can be concluded that Malaysia is not totally free from seismic activities either in peninsular Malaysia or at the east of Malaysia. In 2009, Malaysia Public Work of Department (PWD) felt it was worthwhile to consider seismic design input in new building which are located in medium to high risk earthquake zone. The effect of seismic design implementation on cost of materials is became an important topic to be investigated. In relation to that, this study discusses on the seismic design of reinforce concrete hospital building with consideration of different magnitude of Peak Ground Acceleration (PGA) and different class of ductility. The outcome of the design is the comparison on the amount of steel reinforcement required that is obtained from two different parameters mentioned above compared to non-seismic design. Six models of hospital buildings with consideration of different PGA and ductility class are considered, namely, non-seismic building, medium ductility with PGA of 0.04g, 0.08g, 0.12g, 0.16g and low ductility with PGA of 0.04g. For different magnitude of PGA, the results shows that the percentage difference of steel reinforcement required compared to non-seismic design for beam and column of the whole building had increased from 6%, 116%, 257%, and 290% for PGA equals to 0.04g, 0.08g, 0.12g, and 0.16g respectively. While for different class of ductility, the results shows that the percentage difference of steel reinforcement required compared to non-seismic design had increased from 6% to 145% for ductility class medium and ductility class low respectively. Thus, magnitude of PGA and class of ductility of structure give significant effect to overall amount of steel reinforcement required. Hence, it should be considered in designing a seismic building.